Juridical Review of Abuse of Authority by Law Enforcement Officials in the Process of Investigating Corruption Crimes - Aina Zaskiandra; Alpin Jonatan Siagian; Dhea Lova Br Surbakti; Dirga Mulia Akbar; Idam Malik Sinulingga; Suci Ramadani (International Forum of Researchers and Lecturers, 2026)
This study explores the phenomenon of abuse of authority in the investigation stage of corruption cases, focusing on various violations of practices, causative factors, and implications for justice and legal certainty. The study uses a normative juridical approach through the study of laws and regulations, legal doctrine, and empirical literature to build a comprehensive and systematic analysis. The findings indicate that oversight gaps, weak institutional control, and low integrity of the authorities are the main triggers for actions that go beyond authority, which in turn reduces the effectiveness of evidence and lowers public trust in law enforcement institutions. In addition, the lack of transparency and accountability mechanisms further exacerbates the risk of procedural violations during the investigation process. These conditions can potentially undermine the principles of due process of law and fairness in the criminal justice system. To address this problem, it is necessary to improve internal and external control mechanisms, strengthen supervision by independent institutions, and ensure the consistent implementation of disciplinary measures and legal sanctions against violators. By reinforcing these efforts, it is expected that law enforcement agencies can enhance professionalism, maintain integrity, and restore public confidence in handling corruption cases. (Soekanto & Mamudji, 2020; KUHAP; Corruption Law).